Jogos educativos no Ensino Fundamental: uma prática pedagógica nos anos iniciais / Educational Games in Elementary Education: a Pedagogical Practice in the Early Years - Diniz Coutinho Santos, Kátia; Piazzi Machado, Miriam Raquel; Alves, Alesandra (Revista Internacional de Aprendizaje en Ciencia, Matemáticas y Tecnología, 2015)
ABSTRACT This work aims to present the pedagogical practice of the Project “Educational Games / Maths” as an educational resource for students from the first segment of Elementary School at Colégio de Aplicação João XXIII UFJF. This article presents the pedagogical practice developed in the project “Educational Games / Maths” as a trigger strategy of teaching and learning process, held with students of the first segment of Elementary Education from Colégio de Aplicação João XXIII / Federal University of Juiz de Fora, school that has as principles teaching, research and extension. It is considered that the use of games as a teaching and learning strategy has presented good results as it creates situations that allow students to develop methods of problem solving, stimulating their creativity. This educational resource does not represent an isolated activity within the school field, but a job that is developed within the curricula content, both in mathematics, as in other areas of knowledge. We believe that the production of knowledge that is established among students in developed recreational activities can subsidize educational practices and serve as a reference for other realities. It is taken as the theoretical reference in this work Brougère (2008), Huizinga (2008), Kami and DeVries (1991), Kishimoto (2003) and Lima (2008). This project has been in place since 2001 and has included the participation of graduate students / scholars from UFJF. Partial results show the importance of the games in the construction of knowledge and in the development of multiple intelligences RESUMO Esse trabalho tem como objetivo apresentar a prática pedagógica do Projeto “Jogos Educativos/Matemáticos” como recurso pedagógico para alunos do primeiro segmento do Ensino Fundamental no Colégio de Aplicação João XXIII. Esse artigo apresenta a prática pedagógica desenvolvida no Projeto “Jogos Educativos/Matemáticos” como estratégia desencadeadora do processo de ensino e aprendizagem, realizada com alunos do primeiro segmento do Ensino Fundamental do Colégio de Aplicação João XXIII/Universidade Federal de Juiz de Fora, escola que tem como princípios o ensino, a pesquisa e a extensão. Considera-se que o emprego de jogos como estratégia de ensino e aprendizagem tem apre-sentado bons resultados, pois cria situações que permitem aos alunos desenvolverem métodos de resolução de problemas, estimulando a sua criatividade. Esse recurso pedagógico não representa uma atividade isolada no âmbito da escola, mas um trabalho que se desenvolve dentro dos conteúdos curriculares, tanto na área da Matemática, quanto em outras áreas do conhecimento. Acreditamos que a produção do conhecimento que se estabelece entre os alunos nas atividades lúdicas desenvolvidas podem subsidiar práticas educativas e servir de referência para outras realidades. Toma-se como referencial teórico nesse trabalho Brougère (2008), Huizinga (2008), Kami e DeVries (1991), Kishimoto (2003) e Lima (2008). Este projeto está em vigor desde 2001 e conta com a participação de graduandos/bolsistas da UFJF. Os resultados parciais revelam a importância do lúdico na construção do conhecimento e no desenvolvimento das várias inteligências. Contato principal: katia_kdcs@hotmail.com